Performance evaluation of a taro (Colocasia esculenta) assisted vermifilter for swine wastewater treatment - Justine Carl Abad; Ma. Grace Sumaria (Annals of Tropical Research)
Untreated swine wastewater is one of the main contributors to the problem of water pollution in areas where swine farming is prevalent. Lack of wastewater treatment facilities can cause nutrient buildup in bodies of water, that result in adverse environmental effects such as eutrophication and can cause the buildup of pathogens in bodies of water. This study evaluated the feasibility of a vermifilter using African Night Crawlers (Eudrilus eugeniae) and taro (Colocasia esculenta) in treating swine wastewater. The cylindrical vermifilters each had a diameter of 35cm, 50cm of freeboard, 15cm of soil substrate, and 35cm of gravel of mixed sizes. One vermifilter was planted with taro plants (TAVF) while the other was not (VF). Water samples were collected from the effluent of the respective setups, and were analyzed for electrical conductivity (EC), total dissolved solids (TDS), oxidation-reduction potential (ORP), dissolved oxygen (DO), and pH.